Media of Learning Development using Kinemaster for 10th Grade Students of SMAN 1 Ubud - Gunadi, I Wayan Epri; Putra, I Nyoman Adi Jaya; Juniarta, Putu Adi Krisna (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research aims to develop audio-visual media in the form of videos as learning media using the Kinemaster video editor application to assist students in learning and improving English vocabulary skills during online learning. This study uses Design and Development (D&D) method proposed by Richey and Klein (2007). The students of SMA Negeri 1 Ubud in Gianyar Regency are the subjects of this research. The data collected in this study used four instruments: an interview guide for a teacher, questionnaires for students, document checklist for tenth-grade senior high school syllabus and expert judgment. The score given by the first expert judges was 72, the second expert judges was 85, and the third expert judges was 80. The expert judgment results analyzed using Nurkancana & Sunartana (1992) formula. The developed learning media categorized as good learning media. Thus, the learning media developed using Kinemaster could assist students in learning and improving English vocabulary skills during learning online.